Introducing Toefl And Strategies For Listening Section: A Learning Program At SMA Negeri 1 Siantar - Sabrina, Isabel Selmiola; Pardede, Gabriella; Lumbantobing, Sarah Theodora; Silalahi, Ariel; Aritonang, Bella; Samongilailai, Heltry Firdayati; Sinaga, Yanti Kristina; Hasibuan, Nurainun; Grace, Ernest (Lembaga Penelitian dan Publikasi Ilmiah, Yayasan Almahmudi Bin Dahlan, 2025)
This mini research Introducing TOEFL and Strategies for Mastering the Listening Section: A Learning Program at SMA Negeri 1 Siantar was conducted with 21 eleventh-grade students (Class XI) as participants. The main objective of this study is to provide a structured and available step in preparing students to face academic English requirements, especially the TOEFL Listening section. The method used in this study consists of three stages: preparation, implementation, and evaluation. In the preparation phase, students were introduced to the TOEFL format and the types of listening questions. In the implementation phase, students were trained using listening strategies such as note-taking, predicting content, and managing time. In the evaluation phase, students’ progress and performance were assessed. The results showed a significant improvement in students’ familiarity with the test and their listening comprehension skills. This program highlights the importance of early training and strategic learning in preparing high school students for academic English proficiency tests.